2021
DOI: 10.3390/ph14020146
|View full text |Cite
|
Sign up to set email alerts
|

Zingerone Targets Status Epilepticus by Blocking Hippocampal Neurodegeneration via Regulation of Redox Imbalance, Inflammation and Apoptosis

Abstract: Epilepsy is an intricate neurological disease where the neurons are severely affected, leading to the mortality of millions worldwide. Status epilepticus (SE), induced by lithium chloride (LiCl) and pilocarpine, is the most accepted model for epilepsy. The current work aims to unravel the mechanisms underlying the anti-epileptic efficacy of zingerone (an active ingredient of ginger), which has beneficial pharmacological activities on seizure-induced behavioral, histological, neurochemical, and molecular patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…It is therefore unlikely that the I Na and I Ca,L inhibited by ZO mainly arise from the alteration of the activity of TRP channels by ZO. Moreover, the subsequent application of reduced glutathione (GSH, 10 mM) and superoxide dismutase (SOD, 500 U/mL) failed to modify ZO-induced changes in the amplitude of the I Na and I Ca,L (data not shown), which makes it unlikely that there is a direct link between the inhibitory action of ZO on ionic currents and its antioxidative properties [ 1 , 5 , 6 , 14 ]. However, the production of reactive oxygen species was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore unlikely that the I Na and I Ca,L inhibited by ZO mainly arise from the alteration of the activity of TRP channels by ZO. Moreover, the subsequent application of reduced glutathione (GSH, 10 mM) and superoxide dismutase (SOD, 500 U/mL) failed to modify ZO-induced changes in the amplitude of the I Na and I Ca,L (data not shown), which makes it unlikely that there is a direct link between the inhibitory action of ZO on ionic currents and its antioxidative properties [ 1 , 5 , 6 , 14 ]. However, the production of reactive oxygen species was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study has reported that ZO ameliorates the adverse effects of status epilepticus by blocking hippocampal neurodegeneration via the regulation of redox imbalance, inflammation, and apoptosis [ 5 ]. The blocking of the I Na and I Ca,L evidenced in the present study supports the potential of ZO to attenuate seizure activity [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, our results led us to hypothesize that apoptosis, neuroin ammation, oxidative stress, and astrogliosis were implicated in the Topamax® apparent neurotoxicity. Oxidative stress with neuroin ammation, neural death, and abnormal connections between neurons are possible pathophysiological features [59]. Zingiber o cinale (Zingiberaceae) is used in traditional medicine as an antiepileptic alternative medication that has antioxidant activity and neuroprotective effects [60].…”
Section: Discussionmentioning
confidence: 99%